1979
DOI: 10.1002/1097-0142(197907)44:1<188::aid-cncr2820440131>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A new characteristic karyotypic anomaly in lymphoproliferative disorders

Abstract: A new characteristic chromosome anomaly t(l1; 14)(q14;q32?) in lympho-proliferative disorders (LPD) is described in 4 cases. The extra material was found on a # 14 chromosome (14q+) and belonged to the long arm of one # 11 chromosome in 3 cases and to the long arm of a #14 in the other case. These cases confirm that the distal end of chromosome 14q may function as a "re-ceptor site," according to the hypothesis of Kaiser-McCaw et a2." and also tend to indicate that chromosome #14 may not be unique in showing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Unlike c-rel, however, chromosomal aberrations involving rela are only infrequently found in human lymphoid tumors. There have been sporadic reports of rela gene translocation in nonHodgkin's lymphomas and multiple myelomas, and ampli®cation was observed in a few cases of DLLC (Table 1; Houldsworth et al, 1996;Lai et al, 1995;Van den Berghe et al, 1979). In one multiple myeloma, rela contains a point mutation in its transactivation domain that reduces its transactivation potential (Table 1; Trecca et al, 1997).…”
Section: Rela Gene Alterations In Leukemias and Lymphomasmentioning
confidence: 99%
“…Unlike c-rel, however, chromosomal aberrations involving rela are only infrequently found in human lymphoid tumors. There have been sporadic reports of rela gene translocation in nonHodgkin's lymphomas and multiple myelomas, and ampli®cation was observed in a few cases of DLLC (Table 1; Houldsworth et al, 1996;Lai et al, 1995;Van den Berghe et al, 1979). In one multiple myeloma, rela contains a point mutation in its transactivation domain that reduces its transactivation potential (Table 1; Trecca et al, 1997).…”
Section: Rela Gene Alterations In Leukemias and Lymphomasmentioning
confidence: 99%
“…The t(11;14)(ql3;q32) translocation is an important abnormality associated with B-lymphocytic malignancy (9,32,48,50). Breakpoints at chromosome 14q32 occur in the joining region of the immunoglobulin heavy-chain (IgH) gene (25,46,47).…”
mentioning
confidence: 99%
“…Translocations of either the long arm of chromosome 11 (ql3-+qter) or the long arm of chromosome 18 (q21-*qter) to band q32 of chromosome 14 have been observed in diffuse large-cell lymphoma (12), diffuse small-cell lymphoma (13,14), chronic lymphocytic leukemia of the B-cell type (15), multiple myeloma (16), and follicular lymphoma (13,14). Recently, we have cloned the chromosomal breakpoint of B-cell leukemias and lymphomas with the t(11;14)(q13;q32) translocation (12) and have shown that the breakpoints in three separate tumors with this translocation occurred within a 4-kilobase (kb) stretch of DNA (unpublished observations). We have inferred that at band q13 of human chromosome 11 is located a locus, which we named bcl-J, that is activated by its proximity to the heavy chain locus and is involved in the expression of neoplasia in B cells carrying the 11;14 translocation (17,18).…”
mentioning
confidence: 99%